(untitled) - Mills, Daniel Quinn (New York, 1985)
The product of an exhaustive study of American management practices, here is an authoritative account of the skills and personal and professional characteristics that managers need if they are to succeed in today's highly competitive, internationalized environment. The book addresses the needs, interests and aspirations of the "new breed" of American manager, and tells the stories of how individual managers have made big gains-and losses - for their companies, providing solid models by which managers can hone their own management skills
Keywords: Quản lý công nghiệp,Industrial management; Hoa Kỳ,United States